Does environmental impact vary widely within the same food category? A case study on industrial pizzas from the French retail market. (15th February 2022) - Cortesi, Adeline; Pénicaud, Caroline; Saint-Eve, Anne; Soler, Louis-Georges; Souchon, Isabelle
Abstract: There is an urgent need to reduce the strong environmental impact of food production and consumption, which are expected to increase in the coming years due to the growing world population. Life cycle assessment (LCA) is a known method for environmental evaluation worldwide. In the case of food products, LCAs are often carried out on a single representative of a food category, which does not allow an understanding of possible variations in the environmental impact between products belonging to the same category. We aimed to assess and compare the environmental impact of a wide range of food products belonging to the same food category. The study model chosen was industrial pizza, because of its high consumption worldwide and its large range of recipes, as well as its various storage conditions (fresh or frozen), distributors, and nutritional content. Thus, we assessed the environmental impact of 80 pizzas representative of the 2010 French retail market by LCA, using 1 kg of ready-to-eat pizza as the functional unit and the EF 3.0 method for impact characterization. LCA showed ingredient production to be the stage of pizza production with the highest impact. Moreover, statistical analysis of the results showed that the sector and distribution mode of the pizzas do not appear to have an influence on their environmental impact. On the contrary, the pizza recipes have a significant influence on the environmental impact of industrial pizza. Indeed, pizzas containing beef have a significantly higher environmental impact than the others and the cheese content of pizzas positively correlates with their environmental impact. Finally, we observed that the higher the protein, fat, and saturated fatty acid content of the pizzas studied, the greater their environmental impact in most of the studied environmental impact categories. These results could be useful for LCA practitioners who want to strengthen our knowledge on the environmental impact of food and companies that want to develop more sustainable products, as well as for consumers who want to make more sustainable choices. Highlights: Life Cycle Assessment (LCA) of 80 industrial pizzas have been calculated. Environmental impacts can vary greatly between items from the same food category. Ingredients are the main contributor to the environmental impacts of pizzas. Pizzas environmental impacts are mainly driven by their cheese and beef contents. Pizzas cannot be compared based on the average impacts of their families.